Cultural identity, literacy and language teaching in Mozambique: (mis)matches between nationality and ethnicity (Olhar de Professor, 2023)
The discursive and pedagogical practices of literacy are linked to the autonomous model that conceives language as neutral, discrediting the individual demands. In this paper, from the perspective of the New Literacy Studies, it is elected, as an objective, to analyze how the national and ethnic identity is constituted in the pedagogical practices of teachers. The theoretical framework followed the approaches of Dias (2008), Hall (2000), Patel (2012) and Street (2014), among others. The agency materiality is made up of statements given by teachers analyzed in the light of that perspective, through a qualitative approach. The results suggest that the constitution of national identity relates to the domain of the Portuguese language and the ethnicity with the Bantu languages.
Keywords: Cultural identity. Literacy. Mozambican languages.